The contribution of the Paralympic Games to the development of the qualities of cooperation and competition among primary school students. - FAID, ABD ERRAZAK; MEDJADI, MEFTAH; HAMLAOUI, AMEUR (sports creativity, 2025)
The study aims to know the contribution of the semi-sports games to the development of the qualities of cooperation and competition among primary school students from the viewpoint of the professors of the Institute of Science and Techniques of Physical and Sports Activities. She was chosen randomly, with 17 professors, and the following results were reached: The semi-sports games contribute greatly to the development of the qualities of cooperation and competition among primary school pupils from the viewpoint of professors of the Institute of Science and Techniques of Physical and Sports Activities at the University of Mohamed Boudiaf –Msila.